1991
DOI: 10.1007/bf00317527
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of predation risk under the cover of darkness: Avoidance responses of mayfly larvae to a benthic fish

Abstract: Mayfly larvae of Paraleptophlebia heteronea (McDunnough) had two antipredator responses to a nocturnal fish predator (Rhinichthys cataractae (Valenciennes)): flight into the drift and retreat into interstitial crevices. Drift rates of Paraleptophlebia abruptly increased by 30 fold when fish were actively foraging in the laboratory streams but, even before fish were removed, drift began returning to control levels because larvae settled to the substrate and moved to areas of low risk beneath stones. This drifti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 44 publications
6
50
0
1
Order By: Relevance
“…These patterns suggest that fish constrain activity of grazing invertebrates, whereby the distances that insects venture from refugia differ according to fish species. This interpretation would be consistent with findings that fish modify stream invertebrate behaviors and limit the amount of time foragers spend on exposed surfaces outside of refugia (e.g., Kohler and McPeek 1989, Culp et al 1991, Huang and Sih 1991, McIntosh and Townsend 1994.…”
Section: Discussionsupporting
confidence: 89%
“…These patterns suggest that fish constrain activity of grazing invertebrates, whereby the distances that insects venture from refugia differ according to fish species. This interpretation would be consistent with findings that fish modify stream invertebrate behaviors and limit the amount of time foragers spend on exposed surfaces outside of refugia (e.g., Kohler and McPeek 1989, Culp et al 1991, Huang and Sih 1991, McIntosh and Townsend 1994.…”
Section: Discussionsupporting
confidence: 89%
“…Taller shrubs may have functioned in reducing predation risk at night through concealment or impediment, or may have provided a generally favorable thermal environment in a landscape where cold temperature and high wind occur with frequency (sensu Guthery et al 2005). Temporal shifts in behavior have been noted across taxa and typically reflect differences between day and night in the accessibility of prey or forage resources, the risk of predation, or competition (Culp et al 1991, McMahon and Evans 1992, Reimchen 1998. In this and other human-modified landscapes, information on behavior across the diel cycle gives cause to view effective habitat loss as a spatiotemporal process rather than simply a spatial phenomenon; specifically, animals may select humanmodified landscapes at night but show strong avoidance of these areas during the day (Dzialak et al 2011a;2011b).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, McIntosh and Peckarsky (2004) demonstrated that the mayfly Baetis bicaudatis adjusted its drift behaviour proportionally to the risk imposed by the odours of different fish predators. Studies have also shown Baetis to adjust its drift behaviour along gradients of fish density (Flecker 1992) and in response to simultaneous manipulations of predation and resources (Culp et al 1991;Culp 1994a, 1994b;Hoover and Richardson 2009). These results indicate that Baetis, a highly drift-prone taxa, has a moderately sophisticated response to balance foraging opportunities and predator avoidance using multiple environmental cues.…”
Section: Diurnal Versus Nocturnal Effects On Driftmentioning
confidence: 99%